Evaluation of Thermal Environment Effects on Human Strength: An Empirical Investigation in Controlled Laboratory Conditions - Mohammed Hameeduddin Haqqani; Mohammed Azizuddin; Syed Shuibul Qarnain (Science and Technology: Developments and Applications Vol. 5, 2025)
The thermal environment is an important factor that affects human performance. Research has shown that temperature can have a significant impact on muscular strength and endurance. Understanding the impact of temperature on muscular strength and endurance has important implications for optimizing performance in various settings, including athletic, military, and occupational environments. The goal of this study was to perform an empirical inquiry into the effects of various temperature conditions on muscle strength and endurance. The study assessed the handgrip strength and sit-up endurance of physically active people in a controlled laboratory setting at four distinct temperatures (10°C, 20°C, 30°C, and 40°C). The findings showed that severe temperatures (40°C) had a negative influence on muscle strength and endurance, whereas intermediate temperatures (20°C and 30°C) had a favorable effect. These findings have significance for the design of places requiring peak physical performance, such as athletic facilities, military operations, and workplace safety. Future research could investigate other physical performance factors, assess individual differences in response to thermal conditions, analyse non-linear effects of temperature on performance, and evaluate the impact of thermal environment on physical performance in real-world settings.